Antenna-coupled spintronic terahertz emitters driven by a 1550 nm femtosecond laser oscillator - Nandi, Uttam; Abdelaziz, M. S.; Jaiswal, Samridh; Jakob, Gerhard; Gueckstock, Oliver; Rouzegar, S. M.; Seifert, T. S.; Klaeui, M.; Kampfrath, T.; Preu, Sascha (Applied Physics Letters, 2019)
We demonstrate antenna-coupled spintronic terahertz (THz) emitters excited by 1550 nm, 90 fs laser pulses. Antennas are employed to optimize THz outcoupling and frequency coverage of ferromagnetic/nonmagnetic metallic spintronic structures. We directly compare the antenna-coupled devices to those without antennas. Using a 200 μm H-dipole antenna and an ErAs:InGaAs photoconductive receiver, we obtain a 2.42-fold larger THz peak-peak signal, a bandwidth of 4.5 THz, and an increase in the peak dynamic range (DNR) from 53 dB to 65 dB. A 25 μm slotline antenna offered 5 dB larger peak DNR and a bandwidth of 5 THz. For all measurements, we use a comparatively low laser power of 45 mW from a commercial fiber-coupled system that is frequently employed in table-top THz time-domain systems.
CRIS-Team Scopus Importer:2023-03-27